Manajemen Pendidikan di Era Digital: Tantangan, Peluang dan Efisiensi - Ahmad Khumaidi; Umat Lili Hamdani; Apriliantoni (CV. Creative Tugu Pena, 2024)
This study aims to determine what challenges are experienced by educational management in the digital era in managing educational institutions. In addition to revealing the challenges, the author also tries to open up what opportunities exist in the digital era and its efficiency for the progress and arrangement of educational institutions. In this study, the author uses a qualitative method with an emphasis on literature review to find out or understand in depth the challenges of educational management in the digital era, as well as to identify the challenges and opportunities that arise. Management of education management information systems is a way for leaders and decision makers in the education sector to improve education management in the future.